2016
DOI: 10.1080/13640461.2016.1194567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of artificial re-gassing of aluminium melts after ultrasonic treatment

Abstract: Ultrasonic treatment of aluminium melts is known as an efficient process to remove dissolved hydrogen. Whereas the degassing efficiency of ultrasonic treatment has been extensively reported, the effect of re-gassing after the ultrasonic treatment is much less studied. The present investigation attempts to evaluate the effect of artificial re-gassing of aluminium melts after ultrasonic treatment was applied. The results show an increase in porosity after artificial re-gassing after ultrasonic treatment compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, it may play a role in the process of degassing [38]. It has also been found that the effect of solute metals has a more significant role in grain refinement than UST, although UST does further refine the grain structure [13,43,46,47].…”
Section: Ultrasonic Treatment Key Methodology and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may play a role in the process of degassing [38]. It has also been found that the effect of solute metals has a more significant role in grain refinement than UST, although UST does further refine the grain structure [13,43,46,47].…”
Section: Ultrasonic Treatment Key Methodology and Findingsmentioning
confidence: 99%
“…UST degassing provides advantages over traditional methods as it does not require the extra cost of purging gases and only releases the dissolved hydrogen into the melt. There is extensive literature on UST degassing and it has been found that it can reduce dissolved hydrogen amounts by 40-50% [12,37,38].…”
Section: Degassingmentioning
confidence: 99%